UTBB FD-SOI MOSFET with SELBOX in DTMOS configuration - Da Silva, Jeveson Cardoso [UNESP]; Martins, Everson [UNESP]; Junior, Nilton Graziono [UNESP]; De Andrade, Maria Glória Caño [UNESP] (Journal of Integrated Circuits and Systems, 2022)
For the first time, Ultra-Thin Body and Buried Oxide Fully Depleted Silicon-On-Insulator (UTBB FDSOI) n-channel with Dynamic Threshold MOS configuration (DTMOS) using the SELBOX (Selective Buried OXide) sub-strate was analyzed. The drain and substrate current, transcon-ductance (gm) and Subthreshold Slope (SS) ware compared in the DTMOS mode and the standard biasing configuration for different gap width (WGAP) of SELBOX. Additionally, the out-put conductance and the transconductance gain also studied through numerical simulations. The results indicate that the SELBOX structure in DTMOS mode is competitive candidates for analog applications.
Keywords: Analog per-formance; DTMOS; SELBOX; UTBB SOI